Innovative ultrasound approach to estimate spinal mineral density: diagnostic assessment on overweight and obese women. Issue 1 (1st January 2016) - Casciaro, Sergio; Pisani, Paola; Conversano, Francesco; Renna, Maria Daniela; Soloperto, Giulia; Casciaro, Ernesto; Quarta, Eugenio; Grimaldi, Antonella; Muratore, Maurizio
Abstract : The aim of this study is to assess the accuracy of a novel ultrasound (US) approach for lumbar spine densitometry on overweight and obese women of variable age through a clinical validation study. The US method was originally developed in women with body mass index (BMI) < 25 kg/m 2 . In this study, 382 female patients were recruited (45–80 years, BMI > 25 kg/m 2 ) and underwent dual X‐ray absorptiometry (DXA) of lumbar spine (L1–L4) and an US scan of the same vertebrae L1–L4, performed with a dedicated device providing both echographic images and 'raw' radiofrequency signals. Acquired US data were analysed through a novel automatic algorithm that performed a series of spectral and statistical analyses to calculate bone mineral density employing an innovative method. Diagnostic accuracy of US investigations was quantitatively assessed through a direct comparison with DXA results. The average agreement between US and DXA diagnoses was acceptable for patients aged 45–65 years (81.5%), while a slight decrement was observed for older patients (69.6%), which can be partially due to a decrease in DXA accuracy because of age‐related degenerations. The adopted method has a potential for early osteoporosis diagnosis in people younger than 65 years, independent of their BMI.